Taxing Top CEO Incomes - Ales, Laurence; Sleet, Christopher (American Economic Review, 2016)
We use a firm-CEO assignment framework to model the market for CEO effective labor. In the model’s equilibrium, more talented CEOs match with and supply more effort to larger firms. Taxation of CEO incomes affects the equilibrium pricing of CEO effective labor and, hence, spills over and affects firm profits. Absent the ability to tax profits or a direct concern for firm owners, a standard prescription for high marginal income taxes emerges. However, given such an ability or concern, the optimal marginal tax rates are much lower. (JEL D31, H21, M12)